2014
DOI: 10.1039/c4cp01498g
|View full text |Cite|
|
Sign up to set email alerts
|

Vibrational dynamics and solvatochromism of the label SCN in various solvents and hemoglobin by time dependent IR and 2D-IR spectroscopy

Abstract: We investigated the characteristics of the thiocyanate (SCN) functional group as a probe of local structural dynamics for 2D-IR spectroscopy of proteins, exploiting the dependence of vibrational frequency on the environment of the label. Steady-state and time-resolved infrared spectroscopy are performed on the model compound methylthiocyanate (MeSCN) in solvents of different polarity, and compared to data obtained on SCN as a local probe introduced as cyanylated cysteine in the protein bovine hemoglobin. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 70 publications
6
128
0
1
Order By: Relevance
“…A recent study by van Wilderen et al also showed that MeSCN exhibits a solvent-independent anharmonicity, 61 though the connection with bond polarization was not made. While the anharmonicity may be constant for carbonyls in solvents such as hexanes, DMSO, and D 2 O, there is always some contribution from nonlinear and higher-order Stark effects to vibrational frequency shifts, though their contribution may be small.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by van Wilderen et al also showed that MeSCN exhibits a solvent-independent anharmonicity, 61 though the connection with bond polarization was not made. While the anharmonicity may be constant for carbonyls in solvents such as hexanes, DMSO, and D 2 O, there is always some contribution from nonlinear and higher-order Stark effects to vibrational frequency shifts, though their contribution may be small.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Such probes will extend the observation time window. Independent of that, the azide group is attractive also because of the simple routes it enables to chemically modify the resulting MLs by using straightforward "click"-chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, 2D IR spectroscopy can be applied to characterize any site in any protein by selective labeling of side chains via incorporation of unnatural amino acids functionalized with spectrally resolved vibrational probes, such as cyano (CN), 50, 9496 thiocyanate (SCN), 97 and azido (Az) 93, 98 functional groups. A variety of routes exist for their site-selective incorporation into proteins.…”
Section: Peptide and Protein Structure And Dynamicsmentioning
confidence: 99%